Research Trends On Technology-Assisted Child Sexual Abuse: A 20 Years Bibliometric Analysis - Hermawan, Erwin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Technology-Assisted Child Sexual Abuse (TA-CSA) is a critical issue. This study examines the trends of TA-CSA studies globally to understand the issues. Bibliometric analysis with VOSviewer was conducted on 840 selected journal articles published in the last 20 years from the Scopus database. Between 2002 and 2023, scientific articles on the subject were published by 89 countries, with the US, UK, and Canada being the top 3 countries with the highest publication in TA-CSA. Authors from the US and UK dominate research related to TA-CSA. Research on CSA is more related to medicine, psychology, and social science. TA-CSA research tends to increase, with the highest increase occurring in 2020. Bibliometric analysis also reveals researchers' concerns and research trends regarding TA-CSA. The consistent presence of clusters focusing on TA-CSA highlights the ongoing and persistent nature of this issue. Research in this area continues to explore various aspects, including the prevalence, risk factors, and the impact on victims. It emphasises policy evaluation and victims' access to and accept various forms of protection and assistance.